Cleaning of micro- and ultrafiltration membranes with infrasonic backpulsing. - Shugman, Emad Musbah (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Process Engineering))--University of Stellenbosch, 2009.